Serological evidence for exposure to avian influenza viruses within poultry workers in southern China. (20th February 2017) - de Bruin, E.; Zhang, X.; Ke, C.; Sikkema, R.; Koopmans, M.
Summary: The risk of infection with avian influenza viruses for poultry workers is relatively unknown in China, and study results are often biased by the notification of only the severe human cases. Protein microarray was used to detect binding antibodies to 13 different haemagglutinin (HA1‐part) antigens of avian influenza A(H5N1), A(H7N7), A(H7N9) and A(H9N2) viruses, in serum samples from poultry workers and healthy blood donors collected in the course of 3 years in Guangdong Province, China. Significantly higher antibody titre levels were detected in poultry workers when compared to blood donors for the most recent H5 and H9 strains tested. These differences were most pronounced in younger age groups for antigens from older strains, but were observed in all age groups for the recent H5 and H9 antigens. For the H7 strains tested, only poultry workers from two retail live poultry markets had significantly higher antibody titres compared to blood donors.